Antioxidant Enzymes and Heat-Shock Protein Genes of Green Peach Aphid (Myzus persicae) Under Short-Time Heat Stress - Khurshid, Aroosa; Inayat, Rehan; Tamkeen, Ansa; Ul Haq, Inzamam; Li, Chunchun; Boamah, Solomon; Zhou, Jing-Jiang; Liu, Changzhong (Frontiers in Physiology, 2021)
The management of insect pests under fluctuating temperatures has become an interesting area of study due to their ability to stimulate defense mechanisms against heat stress. Therefore, understanding insect’s physiological and molecular response to heat stress is of paramount importance for pest management. Aphids are ectothermic organisms capable of surviving in different climatic conditions. This study aimed to determine the effects of short-time heat stress on green peach aphid Myzus persicae under controlled conditions. In this study, short-time heat stress treatments at different temperatures 27, 30, 33, and 36°C with exposure times of 1, 3, 6, and 10 h, respectively, on the activities of antioxidant enzymes, including superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), and oxidants, such as malondialdehyde (MDA) and hydrogen peroxide (H2O2), were determined. The results showed that the short-time heat stress significantly increased the content of MDA of M. persicae by 71, 78, 81, and 86% at 36°C for the exposure times of 1, 3, 6, and 10 h, respectively, compared with control. The content of H2O2 increased by 75, 80, 85, and 88% at 36°C for the exposure times of 1, 3, 6, and 10 h, respectively, compared with the control. The SOD, POD, and CAT activities increased by 61, 76, and 77% for 1 h, 72, 83, and 84% for 3 h, 80, 85, and 86% for 6 h, and 87, 87.6, and 88% for 10 h at 36°C, respectively, compared with control. Again, under short-time heat stress, the transcription levels of Hsp22, Hsp23, Hsp27, SOD, POD, and CAT genes were upregulated compared with control. Our results suggest that M. persicae increased the enzymatic antioxidant activity and heat-shock gene expression as one of the defensive mechanisms in response to heat stresses.